Diagnostic Accuracy of Noninvasive Genotyping of EGFR in Lung Cancer Patients by Deep Sequencing of Plasma Cell-Free DNA. (6th January 2020) - Uchida, Junji; Kato, Kikuya; Kukita, Yoji; Kumagai, Toru; Nishino, Kazumi; Daga, Haruko; Nagatomo, Izumi; Inoue, Takako; Kimura, Madoka; Oba, Shigeyuki; Ito, Yuri; Takeda, Koji; et al.
Abstract: BACKGROUND: Genotyping of EGFR (epidermal growth factor receptor) mutations is indispensable for making therapeutic decisions regarding whether to use EGFR tyrosine kinase inhibitors (TKIs) for lung cancer. Because some cases might pose challenges for biopsy, noninvasive genotyping of EGFR in circulating tumor DNA (ctDNA) would be beneficial for lung cancer treatment. METHODS: We developed a detection system for EGFR mutations in ctDNA by use of deep sequencing of plasma DNA. Mutations were searched in >100 000 reads obtained from each exon region. Parameters corresponding to the limit of detection and limit of quantification were used as the thresholds for mutation detection. We conducted a multi-institute prospective study to evaluate the detection system, enrolling 288 non–small cell lung cancer (NSCLC) patients. RESULTS: In evaluating the performance of the detection system, we used the genotyping results from biopsy samples as a comparator: diagnostic sensitivity for exon 19 deletions, 50.9% (95% CI 37.9%–63.9%); diagnostic specificity for exon 19 deletions, 98.0% (88.5%–100%); sensitivity for the L858R mutation, 51.9% (38.7%–64.9%); and specificity for L858R, 94.1% (83.5%–98.6%). The overall sensitivities were as follows: all cases, 54.4% (44.8%–63.7%); stages IA–IIIA, 22.2% (11.5%–38.3%); and stages IIIB–IV, 72.7% (60.9%–82.1%). CONCLUSIONS: Deep sequencing of plasma DNA can be used for genotyping of EGFR in lung cancer patients. In particular, the high specificity of the system may enable a direct recommendation for EGFR-TKI on the basis of positive results with plasma DNA. Because sensitivity was low in early-stage NSCLC, the detection system is preferred for stage IIIB–IV NSCLC.